Action, plurality and politics in Hannah Arendt - Silva, Ricardo George de Araújo (2018)
The present text about action, plurality and politics in Hannah Arendt, hás the pretentions of being na exposure of these concepts as far as it is concerned to Hannah Arendt’s thinking comprehension. Thus, the greatest aimis to present the action category and it’s connection with plurality and public spaces in such demarcation that brings to the surface Arendt unique comprehension about the action as political condition and not as instrument, what it would be connected to the violence. We focuse dour argument on the work: “The Human Condition” and we chose for methodology the bibliographic analysis, then consecrated in the philosophical searches.